Vulnerability to soil loss in the Lajeado Pessegueiro watershed, Brazil - Nascimento Machado, Ludmila (2017)
Geotechnologies present as an important tool in identifying vulnerable areas, assisting in land vulnerability mapping, allowing the spatial distribution of risks caused by soil loss. This study aimed to identify and diagnose the vulnerability of the soil in the Lajeado Pessegueiro watershed, Guarujá do Sul, Santa Catarina State, Brazil, based on the strengths and weaknesses of the environment, to provide input for the planning and environmental and economic management. The vulnerability mapping was developed through integrated environmental analysis with many variables and with the use of a geographic information system that allows the spatial distribution of risk through thematic maps, which can assist in the planning and management of the river basin and farms placed in it. The methodology uses the delimitation of landscape units, and assigns to each thematic variable a value of stability (ranging from 1 to 3) in thematic maps (physiographic, pedological, use and occupation of land and slope). The vulnerability map of soil loss was drawn from the integration of physiographic maps, slope, soil conditions and use and occupation of land. The results showed the predominance with 51.98% of averagely stable/vulnerable areas in watershed and this occurrence is associated mainly by the presence of a balance between the morphogenesis and pedogenesis processes. The results obtained can be used in the development of prevention and enforcement practices and soil management aimed at decreasing soil loss.